(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
In learning any language, short-term memory (STM) plays a critical role in processing spoken input. Language is a complex cognitive system deeply embedded in everyday life, yet our understanding of STM’s exact role in language comprehension remains limited. STM temporarily stores phonological, lexical, and syntactic information long enough to allow for real-time sentence interpretation. However, its limited capacity presents challenges when processing unfamiliar or rapidly presented linguistic sequences in a second language.